Variabilidad temporal de la abundancia de Coralliophila abbreviatay Coralliophila caribaea (Mollusca, Coralliophilidae) en un arrecife coralino del Parque Nacional Morrocoy, Venezuela - del Mónaco, Carlos; Villamizar, Estrella; Narciso, Samuel (Revista de Biología Tropical, 2008)
The mollusks Coralliophilaabbreviata and C. caribaea are coral predators in the Caribbean Sea . We evaluated the temporal variabil-ity of abundance and size structure of C. abbreviata and C. caribaea in Cayo Sombrero, Morrocoy National Park, Venezuelar (September 2004 - August 2005). The density of C. abbreviata and C. caribaeawas evalu-ated monthly by means of two 50- meter long transects paralell to the coast line, at 3 m and 6 m deep; adi-tionally, 30 individuals of C. abbreviatawere collected to measure size. The densities of C. abbreviata at the shallow transect fluctuated between 1.78 ind/m2 in September and 6.26 ind/m2 in May. The densities at the deep transect fluctuated between 4.23 ind/m2 in January and 7.66 ind/m2 in May. The densities of C. caribaea at the shallow transect fluctuated between 0 ind/m2 (except in September) and 0.03 ind/m2 (September) and the densities at the deep transect fluctuated between 0 ind/m2 (October to March and July) and 0.1 ind/m2 (April). Most individuals of C. abbreviata and C. caribaeameasured between 12 and 16 mm and between 10 and 15 mm long respectively.